Impact of accounting conservatism on the informativeness of current stock prices f or future earnings - Eung-Gil Kim; Junyong Shim (Global Business & Finance Review (GBFR), 2023)
Purpose: The purpose of this paper is to examine how accounting conservatism affects the relation between current stock returns, current earnings, and future earnings. Design/methodology/approach: To achieve the purpose of this paper, we divide accounting conservatism into conditional and unconditional conservatism and investigate whether the relation between current stock returns, current earnings, and future earnings is different depending on the type of conservatism. Findings: We find that the current stock returns of firms with strong conditional conservatism contain more information about future earnings. However, our results show that informativeness of current stock returns on future earnings does not change under unconditional conservatism. Research limitations/implications: Even though we use prior research to capture the proxy for accounting conservatism, the extent or magnitude of accounting conservatism may not be properly measured by our proxies. However, despite of these limitations, our results still have the following meanings. Originality/value: Our results suggest that compared to unconditional conservatism, conditional conservatism reflects managerial discretion over timely recognition of bad news and results in faster recognition of the impact of future earnings on current earnings. More specifically, our result indicates that conditional conservatism decreases the informativeness of current stock returns for future earnings due to asymmetric timeliness. And our result also provides indirect evidence that conditional conservatism reflects managerial discretion over timely loss recognition compared to unconditional conservatism, and thereby, deteriorates the informativeness of current returns for future earnings.
Keywords: 650; Conditional conservatism; Unconditional conservatism; Future earnings response coefficient (FERC); Stock return; Earning